Kebangkitan Kembali Kurikulum Islam: Ketika Kurikulum Baru Gagal, Tradisi yang Menang: when New Fails, Tradition Prevails - Miftahussurur, Wildan; Fikri, Muhammad; Muhammad Abdul Hamid (Faiyadhah | Journal of Islamic Education Management, 2025)
This study critically examines the comparative efficacy of traditional and contemporary Islamic education curricula, focusing on knowledge acquisition, pedagogical practices, and character formation. Traditional curricula, exemplified by Dars-i Nizami and Hawza-based models, emphasise rigorous textual engagement, memorisation, dialectical reasoning, and mentorship, fostering deep epistemic understanding and integrated ethical-spiritual development. In contrast, contemporary curricula prioritise interdisciplinary learning, technological integration, and student-centred pedagogies, enhancing engagement and breadth of knowledge while presenting challenges in sustaining epistemic depth and moral formation. Employing a qualitative approach with observational, interview, and document analysis data, this study identifies the strengths and limitations of both models, highlighting the necessity for integrative curriculum design. Findings indicate that hybridised approaches, which combine traditional epistemic rigor with modern pedagogical innovation, offer the most promising pathway for cultivating graduates who are intellectually competent, ethically grounded, and socially adaptable. The study underscores that the future of Islamic education depends on a contextually sensitive and theory-informed synthesis of tradition and modernity, ensuring the continuity of moral, spiritual, and epistemic excellence while addressing contemporary educational demands.